Changes in prop roots and pneumatophores of selected oiled mangroves trees in selected areas of TINMAR, Nueva Valencia, Guimaras - Alvarez, Maria Francesca D. (2009.)
The present paper reports on the monthly monitoring of changes exhibited by the prop roots and pneumatophores of four mangrove species Phizophora mucromata, Rhizophora apiculata, Rhizophora stylosa, and Sonneratia alba, in selected oiled and unoiled areas of TINMAR due to the oil spill. This study aimed to analyze changes in the physical appearance or abnormalities obtained by mangrove aerial root structures affected by the oil spill and and the survival rate and different stress responses of prop roots and pneumatophores after an oil spill covering a six month period which started August until february 2008.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo.
Keywords: Mangroves; Oil spill